2015
DOI: 10.1007/s00726-015-2110-2
|View full text |Cite
|
Sign up to set email alerts
|

Impaired energy metabolism of the taurine-deficient heart

Abstract: Taurine is a β-amino acid found in high concentrations in excitable tissues, including the heart. A significant reduction in myocardial taurine content leads to the development of a unique dilated, atrophic cardiomyopathy. One of the major functions of taurine in the heart is the regulation of the respiratory chain. Hence, we tested the hypothesis that taurine deficiency-mediated defects in respiratory chain function lead to impaired energy metabolism and reduced ATP generation. We found that while the rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 29 publications
5
97
0
5
Order By: Relevance
“…We recently found that rats fed β-alanine exhibit impaired mitochondrial energy metabolism and cardiac weakness [10], effects consistent with the reports of β-alanine-mediated hypotonia. In the present study, we examine the effect of β-alanine exposure on isolated cardiomyocytes and fibroblasts, which are the two major cell types of the heart.…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…We recently found that rats fed β-alanine exhibit impaired mitochondrial energy metabolism and cardiac weakness [10], effects consistent with the reports of β-alanine-mediated hypotonia. In the present study, we examine the effect of β-alanine exposure on isolated cardiomyocytes and fibroblasts, which are the two major cell types of the heart.…”
Section: Introductionsupporting
confidence: 86%
“…We have recently shown that hearts of β-alanine-treated rats exhibit reduced contractile function, an effect related in part to impaired mitochondrial energy metabolism [10]. In the present study, we found that the major site of β-alanine action is complex I of the respiratory chain.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Furthermore, an increased lactate/pyruvate ratio and decreased muscular ATP (adenosine triphosphate) production indicate a poor energy supply in Taut (–/–) compared to wild‐type mice . Likewise, decreased markers of fatty acid oxidation and tricarboxylic acid (TCA) cycle activity but increased markers of glycolysis were observed in taurine‐deficient heart muscle. These results indicate that taurine‐depleted muscles favor glucose as an anaerobic cellular energy supply, while mitochondrial bioenergetics (fatty acid oxidation, the TCA cycle, and oxidative phosphorylation [OXPHOS]) are diminished.…”
Section: Biological Functions Of Taurinementioning
confidence: 99%